2016
DOI: 10.1080/09669582.2015.1134558
|View full text |Cite
|
Sign up to set email alerts
|

Participation and retention in a green tourism certification scheme

Abstract: Abstract:Tourism certification schemes offer a transitional procedure to a more transparent and sustainable tourism product. Engaging current and previous Green Tourism Business Scheme (GTBS) members in Scotland, this research addresses issues of retention affecting progression of sustainable tourism supply. Quantitative analysis tracking GTBS members over three time points reveals 2% growth but conceals significant flux in membership. Retention was calculated at 66%, where business type analysis discloses dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 34 publications
0
24
0
4
Order By: Relevance
“…A significant body of research investigates MAD syndrome, with cost (time and money) among the most frequently cited adoption deterrents (Ayuso 2007; Carasuk, Becken, and Hughley 2013; Jarvis, Weeden, and Simcock 2010; Mair and Jago 2010). Widespread industry unawareness of available programs is another longstanding deterrent (Font and Epler Wood 2007; Dunk, Gillespie, and MacLeod 2016). While this may signify the broad failure of sustainable tourism as an aspirational practice 30 years after the concept’s introduction, it could also indicate inherent problems with certification that dissuade adoption and incentivize alternative QCT pathways.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant body of research investigates MAD syndrome, with cost (time and money) among the most frequently cited adoption deterrents (Ayuso 2007; Carasuk, Becken, and Hughley 2013; Jarvis, Weeden, and Simcock 2010; Mair and Jago 2010). Widespread industry unawareness of available programs is another longstanding deterrent (Font and Epler Wood 2007; Dunk, Gillespie, and MacLeod 2016). While this may signify the broad failure of sustainable tourism as an aspirational practice 30 years after the concept’s introduction, it could also indicate inherent problems with certification that dissuade adoption and incentivize alternative QCT pathways.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Articulation of this diversity, accordingly, facilitates industry engagement with effective QCT practice. This is critical because the QCT widely positioned as the aspirational trajectory—certification programs (Honey 2002; Synergy 2000; Weaver 2006)—has gained minimal industry traction and thus may be limited in its potential to achieve widespread sustainability progress (Dodds and Joppe 2005; Dunk, Gillespie, and MacLeod 2016). It is therefore important to identify alternative modes of QCT practice to unveil other options, alone or in combination, that may be more conducive to diverse industry needs and capacities for sustainable tourism progress.…”
Section: Introductionmentioning
confidence: 99%
“…Duglio et al [17] found that personal awareness of the sustainability issue and improving the corporate image were the main motivation for adoption of the European ecolabel by Italian accommodation establishments. Dunk et al [5] asked 109 members and former members of the GTBS in Scotland about their reasons and expectations for joining. Allowing for multiple answers, 63% gave 'green philosophy and practice' as a reason for joining.…”
Section: Motivations For Adoptionmentioning
confidence: 99%
“…Accommodation providers, such as hotels and campsites, impact the environment in various ways, including water and energy use, impact on the landscape, and disposal of waste and wastewater [1][2][3]. While companies in the accommodation sector increasingly voluntarily implement sustainable business practices, such 'green' production processes may be more costly than conventional ones [4][5][6][7][8]. Furthermore, since green goods are credence goods [9], consumers are not able to recognize environmental attributes when purchasing the product.…”
Section: Introductionmentioning
confidence: 99%
“…Many scholars (e.g., Chen and Tung, 2014;Dunk et al, 2016;Suriñach and Wöber, 2017) have paid more attention to sustainable tourism management and point out that tourism industry brings about a lot of disposable products, which can lead to soil and water pollution.…”
Section: Sustainable Tourismmentioning
confidence: 99%